The Use Of Simon Says Game To Improve Students’ Vocabulary Mastery In Learning English At Sma 1 Juwana - Linda Rahmawati; Arso Setiaji; Ajeng Setyorini (Journal of English Language Learning, 2025)
Game-based learning is an innovative method that boosts vocabulary learning through increased student engagement. This research aims to (a) find out students' vocabulary mastery before they participate in vocabulary practice using the Simon Says game. (b) find out students' vocabulary mastery after they participate in vocabulary practice using the Simon Says game. (c) know significant difference in vocabulary mastery before and after they participate in vocabulary practice using the Simon Says game. This research used a quantitative method with a pre-experimental study in one group pre-test post-test design. The research data was collected using a multiple choice pre-test and post-test measurement technique consisting of 20 multiple choice items. The population of this research was the class X of SMA 1 Juwana in Academic Year 2024/2025. The sample of this research was 32 students of class X-6. The results of this study indicate an increase in scores, with the average pre-test score rising from 57.03 to 83.59 in the post-test. This improvement is supported by the SPSS analysis, which shows a significance value (Sig.) of 0.00, indicating a statistically significant difference before and after the implementation of the Simon Says game in learning vocabulary at SMA 1 Juwana.